TELEMEDICINE IN TIMES OF CORONAVIRUS DISEASE-19 AT A TERTIARY CARE GOVERNMENT HOSPITAL IN UTTAR PRADESH, INDIA - PRIYA, ADITY; VAIBHAV, KUNWAR; SRIVASTAVA, SALIL KUMAR; KUMAR, VIJAY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The present study aimed to describe the common symptoms and diagnosis for each specialty which can be used in future for expansion of teleconsultation services and implementation of the E Sanjeevani model in health care. Methods: This is a cross-sectional observational study which comprises the data collected from various specialties over a 4-month period. The telemedicine consultations were given by the consultants of the concerned specialty in adherence to the telemedicine guidelines issued by the government and mostly generic names of the medicine were advised to the patients. The demographic details, chief complaint of the patient, diagnosis, and treatment were recorded. Results: The total number of calls which was received in 4 months period at the telemedicine center in Government Medical College, Ayodhya, was 4848. Maximum number of calls was attended by the department of obstetrics and gynecology which was 771 (15.9%). Coronavirus disease (COVID-19) had a substantial and transformative influence on routine clinical practice across the entire clinical continuum in a very short period of time. Conclusion: The use of telemedicine emerged as a critical tool to improve the provision of health services. The virtual media and other technologies that can be delivered to patients doorsteps need to strengthened. The trailer which telemedicine showed up in times of COVID-19 can definitely produce a good show in days to come with proper communication between the service provider and receiver.